Case Study Analysis of Stock Market Using Algorithms - Prince Nathan S; Onkar Saudagar; Rutika Shinde (Research Parks Publishing LLC, 2021)
Data Science consists of data cleaning, arranging it in the proper manner, and then analyzing it to get the desired output. It is an interdisciplinary field of study that uses data for various research and reporting purposes to derive insights and meaning out of that data. In today’s economy, it is very important to predict the stock prices and their ups and downs. As we are seeing a lot of people are getting closure towards the stock or the bitcoin-like crypto’s. So there are techniques so that one can predict the appropriate result. There are many algorithms that are available to trace the movement of the market. Big data, Data mining, Data visualization all help to analyze the data and predict the outcome.